Automated genomic sequence analysis of the three collagen VI genes: applications to Ullrich congenital muscular dystrophy and Bethlem myopathy. Issue 2 (2nd February 2005) - Lampe, A K; Dunn, D M; von Niederhausern, A C; Hamil, C; Aoyagi, A; Laval, S H; Marie, S K; Chu, M-L; Swoboda, K; Muntoni, F; Bonnemann, C G; Flanigan, K M; et al.
Abstract : Introduction: Mutations in the genes encoding collagen VI ( COL6A1, COL6A2, and COL6A3 ) cause Bethlem myopathy (BM) and Ullrich congenital muscular dystrophy (UCMD). BM is a relatively mild dominantly inherited disorder with proximal weakness and distal joint contractures. UCMD is an autosomal recessive condition causing severe muscle weakness with proximal joint contractures and distal hyperlaxity. Methods: We developed a method for rapid direct sequence analysis of all 107 coding exons of the COL6 genes using single condition amplification/internal primer (SCAIP) sequencing. We have sequenced all three COL6 genes from genomic DNA in 79 patients with UCMD or BM. Results: We found putative mutations in one of the COL6 genes in 62% of patients. This more than doubles the number of identified COL6 mutations. Most of these changes are consistent with straightforward autosomal dominant or recessive inheritance. However, some patients showed changes in more than one of the COL6 genes, and our results suggest that some UCMD patients may have dominantly acting mutations rather than recessive disease. Discussion: Our findings may explain some or all of the cases of UCMD that are unlinked to the COL6 loci under a recessive model. The large number of single nucleotide polymorphisms which we generated in the course of this work may be of importance in determining the major phenotypic variability seen in this group of disorders.